Past, present, and expected hydro-morphologic evolution of the Bahia de Samborombon (Argentina) by remote sensing data - Braga, Federica (2012)
Hydro-geomorphologic setting of coastal areas is the result of complex interactions between marine and continental processes. Lowland morphologies make coastlands the zones at highest hydrogeological risk because of flooding, land subsidence, and saltwater contamination (e.g., Pousa et al. 2007). As many studies have predicted a significant increase of eustacy, sea level rise (SLR) is the most relevant problem affecting coastal lowlands. The wetland of the Samborombon Bay (Argentina) is a Ramsar natural reserve affected to periodic floods due to rainfall, runoff, tidal fluctuations, and storm surges. In this work, we show preliminary results of a project aimed at understanding the effect of expected SLR scenarios on the hydromorphologic setting of the Samborombon Bay. In particular, the outcomes of the first step of the research, i.e., the remote sensing analysis, are illustrated.